Palliative care in glioma management. Issue 6 (November 2019) - Oberndorfer, Stefan; Hutterer, Markus
Abstract : Purpose of review: The concept of palliative care is becoming increasingly important in the management of glioma patients. However, the right time for implementation, as well as the individual degree of integration of palliative care aspects, are still a matter of debate. This review updates recent evidence of palliative care in glioma and raises questions for future developments. Recent findings: According to the disease-specific aspects of palliative care in glioma management, there is an increasing need for a specialized 'neurooncological' palliative care approach. The implementation of palliative care for glioma patients and caregivers avoids unnecessary hospitalization and reduces health-related costs. Moreover, palliative care may be offered in different settings (inpatient/outpatient) according to local health structures, but definitely improves the QOL of glioma patients and their caregivers. Summary: There are considerable differences between countries with respect to palliative care in glioma. Major aspects of good-quality care throughout the countries are optimized symptom control, support for patients and proxies by an interdisciplinary team and to provide realistic information to patients and caregivers. The availability of neurooncological palliative teams and multidisciplinary support programs increases well being of glioma patients and caregivers as well as releases pressure on healthcare systems.